The hydrogen Lyman α line shape in the exospheres of terrestrial objects in the solar system - Bhattacharyya, Dolon; Thiemann, Edward M. B.; Machol, Janet; Cucho-Padin, Gonzalo; Chatterjee, Sabyasachi; Harris, Walter; Mierkiewicz, Edwin (Frontiers in Astronomy and Space Sciences, 2025)
The exospheres of all objects are mostly made of atomic hydrogen. Because the Sun is bright in Lyman α, the properties of the H atoms in the exospheres of certain terrestrial solar system objects can be studied by analyzing the resonantly scattered solar Lyman α emission by these exospheric H atoms. This emission is optically thick in the exospheres of all planets in our solar system except Mercury. This makes it complicated to derive the true characteristics (number density distribution, energy distribution) of the H atoms present in these exospheres. While radiative transfer (RT) models have been used extensively to derive the characteristics of exospheric H atoms by modeling the line-integrated Lyman α intensity measured by spacecrafts via remote sensing, the models often fail to resolve discrepancies between the observed emission intensity and the simulated value. This is because of the various assumptions that are made in the RT models about the inherent characteristics of the H atoms and the corresponding Lyman α lineshape. Our knowledge about the characteristics of the H atoms can be significantly improved by understanding what the true lineshape of the H Lyman α line may be for various conditions. This can then be used to resolve the discrepancies between the modeled and the observed intensities for planetary exospheres. Here we present a detailed study on the shape of the exospheric Lyman α emission line for various conditions like change in altitude, temperature, non-isothermality, asymmetry, and presence of non-thermal atoms. These detailed line profiles are being used to determine H density distribution in Earth’s exosphere from analysis of absorption of the solar Lyman α line by geocoronal H as measured by remote sensing satellites. This theoretical analysis also highlights the advantages of obtaining highly resolved H Lyman α emission line measurements from the exospheres of certain terrestrial objects in our solar system.